Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Pengendalian Internal Terhadap Kualitas Laporan Pertanggungjawaban BOP pada TK Swasta di Kabupaten Buleleng - Kharismayani, Kadek Mas; Kurniawan, Putu Sukma (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the effect of human resource competence, the use of information technology and internal control on the quality of the Operational Assistance Operational Assistance (BOP) accountability report on private kindergartens in Buleleng Regency. This type of research is a quantitative study whose source of data comes from primary data in the form of distributing questionnaires directly to respondents. The population in this study are all private kindergartens institutions that have received Operational Assistance Operational Assistance (BOP) funds in Buleleng Regency. The sample chosen in this study is using the Slovin formula so as to get a total of 66 samples. Data analysis techniques consist of: descriptive analysis, data quality test, classic assumption test, and hypothesis testing. Where in the hypothesis test includes multiple linear regression test, t test and test the coefficient of determination with the help of SPSS version 20 for windows. The results of this study indicate that the competence of human resources has a positive effect on the quality of the BOP accountability report, the use of information technology has a positive effect on the quality of the BOP accountability report and internal control has a positive effect on the quality of the BOP accountability report.